Coordination of operations planning in supply chains: a review. (1st January 2013) - Taghipour, Atour; Frayret, Jean-Marc
Supply chains are networks of loosely coupled business units characterised by distinct, yet mutually interdependent, planning decision domains. The main question that arises in the management of these networks is the coordination of supply chain members' operations with minimum exchange of information. In practice, supply chain operations are generally coordinated and planned hierarchically, through the central and aggregated control of a corporate planning unit, which requires a high degree of information exchanges, or through the relatively inefficient upstream planning approach, in which operations are planned and the derived dependent demand is sent to suppliers. High degree of information exchanges lead to difficulties when independent members do not want to share information, such as cost, profit margin, inventory level or capacity utilisation. In order to address these difficulties, decentralised approaches of coordination of operations planning decisions based on some minimal information sharing have been proposed in many academic disciplines. This paper first proposes a systematic review of these approaches, and then outlines some research opportunities.